Core depth determination of a slightly buried Si-wire waveguide with a reduced bend loss. (24th June 2021) - Aso, Tatsuya; Ishiguro, Takehiro; Yamauchi, Junji; Nakano, Hisamatsu
Abstract: The effects of adjusting the distance between a core and an air-cladding interface on the propagation properties are investigated in a bent Si-wire waveguide. The eigenmode analysis is carried out using the imaginary-distance beam-propagation method based on Yee's mesh in the cylindrical co-ordinate system. The pure bend loss (PBL) is evaluated as a function of core depth for several core aspect ratios. Since a waveguide bend causes polarization coupling, the polarization crosstalk (PCT) is also evaluated by the propagation analysis with the aid of the FDTD method. It is found that a core depth with a minimized PBL exists for the TM mode when the air-cladding interface is placed at the position where the field amplitude decays to approximately 5% of its peak, with a PCT being less than −30 dB.